The effects of inward and outward FDI on domestic investment:Evidence using panel data of ASEAN-8 countries. - Tan, Bee Wah; Goh, Soo Khoon; Wong, Koi Nyen * (Taylor & Francis, 2016)
In view of the changing FDI landscape, in particular, a drastic increase in outward FDI from developing and transition economies in recent years, this paper attempts to explore the possible impacts of outward FDI other than domestic savings and inward foreign direct investment on domestic investment. The major contribution of this study is that it is the first effort to empirically analyse the short- and long-run effects of the outward FDI using panel data of ASEAN–8 countries, which could provide useful policy implications for governments at both regional and international levels to achieve inclusive growth and sustainable development. Using pool mean group analysis, this paper finds that the gross domestic saving, inward FDI and outward FDI have a positive long-run impact on the gross domestic investment even though their long-run estimates are inelastic. The empirical study reveals that both inward FDI and outward FDI, to some extent, are complementary to the gross domestic investment.